Narrations that Sheick Ibn Al-Qaysarani –may Allah have Mercy on him – Ruled on by Saying: ( Its Chain of Transmission is Good ) in his Book Dhakhirat Al-Huffaz (Islamic Sciences Journal, 2025)
Praise be to Allah, and peace and blessings be upon the Messenger of Allah. This research aims to study and analyze the concept of "its chain of narration is good" in the science of hadith. The first chapter discusses the definition of the term and its uses in hadith books, and the difference between it and similar terms such as "good chain of narration" and "authentic chain of narration". It was found that this term was not one of the agreed-upon terms among scholars, but it was used in some late sources to indicate a middle rank between authentic and good.The second chapter provides a definition of Sheikh Ibn al-Qaisrani, highlighting his scientific status and role in the science of hadith, in addition to studying his book "Dhakirat al-Huffaz" and its importance in classifying hadiths. The study showed that Ibn al-Qaisrani was one of the scholars who were interested in critically examining chains of narration accurately, and that his book represents a valuable scientific addition in this field.The research concluded that it is necessary to clarify the implications of uncommon hadith terms, conduct comparative studies between the classifications of hadith scholars, and call for a comprehensive scientific study of the book "Dhakirat al-Huffaz" to verify its texts and study its hadith rulings.
Keywords: Narrations, Ibn al-Qaysarani, chain of transmission, good, treasure of hadith preservers